2016
DOI: 10.1016/j.redox.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin and oxidative stress in humans: A randomized, double-blinded, placebo-controlled clinical trial

Abstract: Simvastatin reduces the blood concentration of cholesterol by inhibiting hydroxymethylglutaryl-coenzyme A reductase, the rate-limiting enzyme in cholesterol synthesis, and thereby reduces the risk of cardiovascular disease. In addition, simvastatin treatment leads to a reduction in fluxes in mitochondrial respiratory complexes I and II and might thereby reduce the formation of reactive oxygen species, which have been implicated in the pathogenesis of arteriosclerosis. Therefore, we hypothesized that simvastati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 25 publications
3
47
0
Order By: Relevance
“…However, a study performed in coronary artery disease patients where Ezetimibe/Simvastatin 10/20 mg was compared to Simvastatin 80 mg as monotherapy demonstrated that inflammation biomarkers (CRP, IL-6, monocyte chemoattractant protein-1, and soluble CD40) were unaltered after 6 weeks of treatment, probably explained by the theory that the target of statins resides on oxidative stress rather than inflammatory response [136]. A study performed in healthy male subjects treated with Simvastatin monotherapy showed no changes in oxidative stress to nucleic acids, LPO, and plasma antioxidants [137], probably due to the lack of free radicals increase, since Ezetimibe alone has been shown to reduce 8-isoprostanes and reactive oxygen metabolites levels only in hypercholesterolemic patients with high oxidative stress at baseline, but not in those with near-normal oxidative status [138]. Rosuvastatin 20 mg was assessed in 17 patients with type 2 DM and DPN, and a reduction of Neuropathic Symptoms Score (NSS) and NCS were observed after 12 weeks of treatment, along with a significant reduction in LPO but no changes in nerve growth factor beta [139].…”
Section: Diabetic Polyneuropathymentioning
confidence: 99%
“…However, a study performed in coronary artery disease patients where Ezetimibe/Simvastatin 10/20 mg was compared to Simvastatin 80 mg as monotherapy demonstrated that inflammation biomarkers (CRP, IL-6, monocyte chemoattractant protein-1, and soluble CD40) were unaltered after 6 weeks of treatment, probably explained by the theory that the target of statins resides on oxidative stress rather than inflammatory response [136]. A study performed in healthy male subjects treated with Simvastatin monotherapy showed no changes in oxidative stress to nucleic acids, LPO, and plasma antioxidants [137], probably due to the lack of free radicals increase, since Ezetimibe alone has been shown to reduce 8-isoprostanes and reactive oxygen metabolites levels only in hypercholesterolemic patients with high oxidative stress at baseline, but not in those with near-normal oxidative status [138]. Rosuvastatin 20 mg was assessed in 17 patients with type 2 DM and DPN, and a reduction of Neuropathic Symptoms Score (NSS) and NCS were observed after 12 weeks of treatment, along with a significant reduction in LPO but no changes in nerve growth factor beta [139].…”
Section: Diabetic Polyneuropathymentioning
confidence: 99%
“…We used validated and highly specific ultraperformance liquid chromatography tandem mass spectrometry to detect 8-oxoGuo levels, which were then compared with the levels of 8-oxodG (the biomarker for DNA modification by oxidation) in spot urine samples corrected for urinary creatinine (21). The validation procedures were in accordance with the U.S. Food and Drug Administration guidelines, and the lower limit of quantification was 1.0 nmol/L for both 8-oxoGuo and 8-oxodG (21). According to recently published data, the accuracy of this method was 98.7% for 8-oxoGuo and 95.7% for 8-oxodG (21).…”
Section: Measurements Of Urinary Nucleic Acid Biomarkersmentioning
confidence: 99%
“…The validation procedures were in accordance with the U.S. Food and Drug Administration guidelines, and the lower limit of quantification was 1.0 nmol/L for both 8-oxoGuo and 8-oxodG (21). According to recently published data, the accuracy of this method was 98.7% for 8-oxoGuo and 95.7% for 8-oxodG (21). The average within-day precision was 2.9% for 8-oxoGuo and 3.7% for 8-oxodG; average between-day precision was 1.5% for 8-oxoGuo and 3.4% for 8-oxodG (21).…”
Section: Measurements Of Urinary Nucleic Acid Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though statins lower calcium-induced oxidative modifications [43], simvastatin did not reduce oxidative modifications in healthy humans [44]. The limited and inconsistent literature exploring a possible antioxidant effect of statins are not sufficient to rule out whether the reversed effect of statins in the CLARICOR results could be explained by an antioxidant effect by the statins.…”
Section: Placebomentioning
confidence: 96%